VD_FINDINFO HC / 2014 / 576 vom 6. Juni 2014 - VD Tribunal cantonal (2014)
ACTION EN PARTAGE SUCCESSORAL, EXPERTISE, NOTAIRE, VALEUR VÉNALESENS GÉNÉRAL | 602 CC, 604 CC, 617 CC, 618 CC, 570 CPC, 572 CPC, 90 al. 1 CPC, 5 al. 3 Cst.